FOOD HABIT AMONG ELEMENTARY SCHOOL CHILDREN IN URBAN BOGOR - Evy Damayanthi; Cesilia Meti Dwiriani; Lilik Kustiyah; Dodik Briawan (Food and Nutrition Society of Indonesia, 2010)
Food habit strongly predicts individual nutritional status. It is largely influenced by family food habit and family socioeconomic, partly by nutrition education learning in the school. Objectives of this study were to analyze elementary school children eating habit and examine whether it relates to family socioeconomic and nutritional status.One hundred elementary school children, and their mother, from one school in urban Bogor were chosen purposively according to SIBERMAS Program criteria (i.e. grade 4th and 5th, morning school, having UKS program and not havingcanteen). Self administered, structured pre-coded questionnaire were used to collect the data. Nutritional status was assessed using weight and height, and body mass index for age (BAZ) and height for age (HAZ) were then calculated using AnthroPlus software developed by WHO (2009). School children were 8-11 years old (mean 9.37 + 0.66 years), more girls (54%), and mostly had normal nutritional status using both indexes (72% for BAZ and 95% for HAZ). School children were commonly from middle class as indicated by father education (sarjana) and mother (senior high school). Almost all school children (99%) knew breakfast was important and 81% of them ate breakfast. Only 32% school children brought lunch box everyday although 92% stated their habit to bring lunch box to school. Buying snack in school was also common among school children. Generally school children ate rice 3 times a day (2.95 + 0.97) with fish, meat, chicken (2.47 + 1.14), tempe and tofu (2.22 + 1.10), vegetables (2.25 + 0.76) and fruits (2.37 + 1.31). There was a tendency overweight and obese school children eat more rice although statistically not significant. On average, school children drank milk more than twice daily (2.34 + 0.98), plain water more than 7 glasses daily (7.34 + 4.10), exercise 3 times weekly (3.02 + 2.16) and no difference were observed between nutritional status and family socioeconomics. School children food habit were strongly supported by mother behavior especially in providing breakfast, lunch box and guiding their children in choosing snack food. School children from middle class in urban Bogor had relatively good food habits which weresupported by mother behavior. This study found no relationship between family socioeconomic and nutritional status on school children food habit.